The relative importance of intelligence and motivation as predictors of school achievement: a meta-analysis - Reschke, Katharina; Becker, Nicolas; Spinath, Birgit (Educational research review, 2018)
This meta-analysis summarizes 74 studies (N=80,145) that simultaneously examined the predictive power of intelligence and motivation for school achievement. First, we found average correlations between intelligence (r=0.44) and motivation (r=0.27) with school achievement and between intelligence and motivation (r=0.17). Moderator analyses showed that the correlation between motivation and school achievement was higher for expectancies than for values. No moderator effects were found for grade level, school form or gender. Second, in a path model, 24% of variance in school achievement was explained overall. From this overall explained variance in school achievement, 66.6% was uniquely explained by intelligence and 16.6% uniquely by motivation, whereas the two predictors commonly explained 16.6%. Thus, the results show that both intelligence and motivation contribute substantial, unique shares to the prediction of school achievement as well as an additional share of commonly explained variance.
Gesehen am 06.05.2019